Recent Developments in Peptidyl Diaryl Phoshonates as Inhibitors and Activity-Based Probes for Serine Proteases - Marta Maślanka (Pharmaceuticals, 2019)
This review presents current achievements in peptidyl diaryl phosphonates as covalent, specific mechanism-based inhibitors of serine proteases. Along three decades diaryl phosphonates have emerged as invaluable tools in fundamental and applicative studies involving these hydrolases. Such an impact has been promoted by advantageous features that characterize the phosphonate compounds and their use. First, the synthesis is versatile and allows comprehensive structural modification and diversification. Accordingly, reactivity and specificity of these bioactive molecules can be easily controlled by appropriate adjustments of the side chains and the leaving groups. Secondly, the phosphonates target exclusively serine proteases and leave other oxygen and sulfur nucleophiles intact. Synthetic accessibility, lack of toxicity, and promising pharmacokinetic properties make them good drug candidates. In consequence, the utility of peptidyl diaryl phosphonates continuously increases and involves novel enzymatic targets and innovative aspects of application. For example, conjugation of the structures of specific inhibitors with reporter groups has become a convenient approach to construct activity-based molecular probes capable of monitoring location and distribution of serine proteases.